Minat Belajar Bahasa Arab Melalui Penggunaan Media WhatsApp Siswa Kelas XI MA Ma'arif Lasepang Kab. Bantaeng - Ainun Salsabila; Arief Fiddienika (Fakultas Teknik Universitas Negeri Makassar, 2021)
This research is a descriptive quantitative study that aims to determine the high or low interest in learning Arabic for class XI students of MA Ma'arif Lasepang Kab. Bantaeng through the use of WhatsApp media. The independent variable in this study is WhatsApp media and the dependent variable is students' interest in learning. The population in this study were all students of class XI MA Ma'arif Lasepang, and the samples were class XI MIPA 1 with 16 students and XI IPS 1 with 18 students. The research data were obtained by giving a Likert scale about students' learning interest in terms of intrinsic and extrinsic factors. The data analysis technique in this study used the percentage technique. Based on the results of data analysis regarding interest in learning Arabic through the use of WhatsApp media for class XI MA Ma'arif Lasepang students, it is known that of the 34 students who became the sample, none of the students with very high interest, there are 3 students with high interest (8.8%), there are 13 students with moderate interest (38.3%), 18 students with low interest (52.9%), and none of the students with very low interest. Keywords: interest in learning, WhatsApp, learning media, Arabic Language